Macroeconomic determinants of stock market performance: Evidences from a Malaysia and United States / Aqeel Mohtar and Shazlin Iryanti Saruddin - Mohtar, Aqeel; Saruddin, Shazlin Iryanti (Faculty of Business Management, 2016)
This study is focusing on the effect of macroeconomic determinants towards stock market performance in Malaysia and United States. The purpose of this study is to study the relationship between dependent variable and independent variables and identify the most significant factor that affecting the stock market performance in Malaysia and United States. The data are collected quarterly data from period of 1997:Q1 to 2015:Q4. The data are tested using Unit Root Test, Panel Data Regression and Diagnostic tests to find the relationship between macroeconomic determinants variables such as money supply, interest rates, exchange rates, gross domestic product and industrial production index towards Malaysia and United States stock market performance. The results obtained from Pool OLS estimation reveal that money supply, interest rate, gross domestic product and industrial production index have positive relationship on the stock market performance while exchange rate has negative relationship on the stock market performance. This shows that the United States and Malaysian stock market are sensitive to changes in the macroeconomic variables. Furthermore, based on the result, money supply is the most significant factor that affecting the stock market performance.